The discourse of the Western media in covering the events of the Middle East (the report of the British agency "Reuters" on the situation in Iraq as a model) - عيسى متقي زاده; سيد علاء نقي زاده (آداب الكوفة, 2017)
The analysis of political discourse has an important place in media circles, especially in the field of editing news and news reports, as it is intended to clarify the special events related to communications, and the formation and change of political discourse systems. In order to analyze texts and discursive events in order to reach discourse systems and social systems, texts and events within the political and social fields must be studied, by relying on cultural information and written words in political discourse.